Studies on Yield, Economics and Energetics of Rice (Oryza sativa L.) in Relation to Crop Establishment Methods and Nutrient Management Practices - Mohanty, Tushar Ranjan; Maity, Swapan Kumar; Roul, Pravat Kumar; Sahoo, Kishore Chandra (International Journal of Bio-resource and Stress Management, 2023)
Field experiments were conducted during wet seasons of 2009 and 2010 to evaluate three rice crop establishment methods viz. system of rice intensification (SRI), drum seeding (DS) and conventional transplanting (CT) under three nutrient management practices viz. RDF (80:40:40 N: P2O5: K2O kg ha-1) through inorganic fertilizers, integrated nutrient management (INM) i.e. 50% of RDF through inorganic fertilizers+50% of R.D.F. through organic sources (based on nitrogen requirement) and organic management (OM) i.e. 100% of R.D.F. through organic sources (based on nitrogen requirement). SRI registered significantly higher leaf area index, dry matter accummulation, root dry weight and root volume over DS and CT except plant height for CT; further18 and 26% higher grain yield than CT and DS, respectively. The crop supplied with INM recorded the highest grain yield (6435 kg ha-1) which was higher by 11.9 and 19.2% over RDF and OM, respectively. The highest gross return (` 77925 ha-1), net return (` 43033 ha-1) and return ` (2.28) were obtained from SRI. The energy output, energy productivity and the energy ratio were the highest with SRI whereas the CT and DS recorded statistically comparable values of energy indices. SRI with INM recorded the highest productivity (7299 kg ha-1), gross return (` 85216 ha-1), net return of (` 50274 ha-1) and energy productivity (644.2 kg-1 MJ×103 ha-1).